PARADOKS DIGITALISASI DI TEMPAT KERJA PEMICU BORE-OUT DAN RENDAHNYA KEPUASAN KERJA KARYAWAN - Muhammad Fajri; Roza Elfira; Nelson Nelson (Komunitas Manajemen Kompetitif, 2025)
The digital era demands that every company integrate technology into its work systems. Society 5.0, with its people-centered approach, advocates leveraging technology to achieve employee well-being. The reality on the ground suggests the opposite: digitalization is actually leading to employee bore-out, a phenomenon researchers call the